A tale of two regions: comparing clinical features and outcomes in pediatric enthesitis-related arthritis - Fatma Gül Demirkan; Vafa Guliyeva; Özlem Akgün; Hanene Lassoued Ferjani; Dorra Ben Nessib; Kawther Maatallah; Dhia Kaffel; Wafa Hamdi; Nuray Aktay Ayaz (Pediatric Rheumatology Online Journal)
Abstract Background Enthesitis-related arthritis (ERA) may exhibit a distinct disease spectrum on the basis of ethnic origin. The pediatric rheumatology teams from the Istanbul Medical Faculty and Tunisia Kassab Institute engaged in collaboration via the Second Sister Hospital Initiative of the European Society of Pediatric Rheumatology (PReS) to investigate the clinical characteristics and outcomes of children with ERA. Methods The medical records of patients with the diagnosis of ERA were reviewed retrospectively. The Juvenile Spondyloarthritis Disease Activity Index (JSpADA) was the tool for assessing disease activity. In addition to clinical and laboratory findings, treatments and disease outcomes were compared. Results A total of 94 children with ERA were enrolled (45 Tunisian, 49 Turkish). Sex and age at disease onset were similar between the groups. Heel pain (8.8% vs. 61.2% for Tunisia vs. Türkiye, p = 0.03) and enthesitis (40% vs. 69.3% for Tunisia vs. Türkiye, p = 0.03, p = 0.8) were more common in Turkish children. Conversely, the rates of sacroiliac tenderness, suggesting clinical sacroiliitis (91.1% vs. 55.1% for Tunisia vs. Türkiye), and axial disease (97.8% vs. 55.1% for Tunisia vs. Türkiye) were significantly greater in Tunisian children (p = 0.002 and p < 0.001, respectively). Overall, 45.7% of the cohort was HLA-B27 positive, including 32% of Turkish patients and 60% of Tunisian patients (p < 0.001). HLA-B27 positivity did not influence age at disease onset (p = 0.45) but was associated with a longer diagnostic delay of the disease (p < 0.001). Nearly half of the Turkish children received biologics during the disease course, whereas only 8.9% of the Tunisian children did. While the median JSpADA scores at disease onset were similar between the groups, Turkish patients had significantly lower scores at the last visit than Tunisian patients did (p < 0.001). Conclusions This study highlights notable differences in the clinical features and outcomes of ERA among Turkish and Tunisian children, emphasizing the potential influence of ethnic and regional factors on disease presentation and management. Variations in HLA-B27 positivity and treatment approaches, including the use of biologics, further underscore the need for tailored strategies in managing ERA across diverse populations.